Elevated levels of plasma collagen priple helix repeat-containing (CTHRC1) protein correlates with increased granul ocytopoiesis and higher rheumatoid arthritis disease severity score - Myngbay, A.; Bexeitov, Y.; Adilbayeva, A.; Yevstratenko, B. P.; Aitzhanova, R. M.; Otarbayev, N. K.; Adarichev, V.A. (My University, 2016)
Monitoring and suppressing activity of the pathological granulating pannus tissue is essential for Rheumatoid Arthritis (RA) management. Synovial joints pain and tissue destruction is a derivative of the pannus activity. In a mouse model for RAwe found CTHRC1, a secreted and circulating protein, to be inducible in arthritis and correlated with the disease severity. We performed a clinical investigation to ascertain the role of CTHRC1 in the progression of the disease.
Keywords: Rheumatoid Arthritis